1979
DOI: 10.1128/aem.37.4.744-749.1979
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of pollution indicator organisms in rural potable water

Abstract: A total of 460 water samples were randomly drawn from the potable water supply sources of rural communities in three counties of South Carolina. About 10% of the population, not incorporated in municipalities, was sampled. The samples were tested for total coliforms, Escherichia coli, and fecal streptococci. Significant levels of these pollution indicator organisms were detected in almost all the water supplies. Total coliforms were the most common, and only 7.5% of the water supplies were uncontaminated. E. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Fecal coliforms were detected in almost one-third of the water supplies (Table 1), a lower incidence than the 48% reported by Sworobuk et al (52) during a previous study of water systems in this study area. In comparison, Sandhu et al (43) reported detection of fecal coliforms in 43% of groundwater supplies surveyed in South Carolina.…”
Section: And Discussionmentioning
confidence: 97%
“…Fecal coliforms were detected in almost one-third of the water supplies (Table 1), a lower incidence than the 48% reported by Sworobuk et al (52) during a previous study of water systems in this study area. In comparison, Sandhu et al (43) reported detection of fecal coliforms in 43% of groundwater supplies surveyed in South Carolina.…”
Section: And Discussionmentioning
confidence: 97%
“…Water quality surveys of domestic wells in some unsewered areas in North America have produced evidence of widespread chemical and microbial contamination of groundwaters (Woodward et al 1961;Hickey & Duncan 1966). Some studies have specifically attributed deterioration in groundwater quality with respect to determinants such as nitrates, detergents, and coliform bacteria to individual household cess pools and septic tank drainfields (Smith & Myott 1975;Sandhu et al 1979;De Walle & Schaff 1980). Disease outbreaks, attributable to the ingestion of contaminated groundwater, have been reported by a number of authors and recent cases in North America have been reviewed by Craun (1979).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, total plate count bacteria were isolated and identified. Although other rural drinking water supplies have been sampled (20,27), the present report is the first seasonal study of drinking water supplies conducted in a recently populated rural neighborhood zoned by modern methods.…”
mentioning
confidence: 99%